GESTATIONAL KIDNEY DAMAGE: IMPAIRED GLUCOSE REABSORPTION DURING PREGNANCY AND THE INTEGRATION OF SCIENTIFIC ACHIEVEMENTS INTO THE TRAINING OF OBSTETRICIANS AND GYNECOLOGISTS - Fatkulina G. R (Uzbekistan Open Conference, 2025)
Pregnancy is accompanied by significant changes in the body’s metabolic and excretory functions. One common physiological change is the appearance of glucose in the urine despite normal blood sugar levels. This condition is associated with a temporary decrease in the kidneys’ ability to completely return glucose to the blood. This article examines the causes and characteristics of this phenomenon, its significance for the health of the pregnant woman and fetus, and issues of differential diagnosis with gestational diabetes. Particular attention is paid to how modern knowledge of the natural sciences and new educational technologies can be used to improve the training of obstetricians and gynecologists. Practical recommendations for teachers and physicians are provided.
Keywords: pregnancy; kidneys; glucose; glucosuria; medical education; integration of sciences